TEACHING VOCABULARY OF CLASSROOM OBJECTS THROUGH FLASHCARD TO STUDENTS AT SMPN 46 PALEMBANG - Risnayanti, Risnayanti; Susanto, Susanto; Aprianto, Yayan (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2017)
Abstract: This study aimed to find out whether or not flashcards in teaching vocabulary of classroom objects is effective. The population of this research is all of the seventh grade students of the State Junior High School 46 of Palembang. Sampling technique used was convenient sampling technique. Weak experimental was administered to one group of students, it meant that the study did not research to compare two different groups. The method was implemented in the form of actual teaching process to sample students. The students were given materials through flashcard. At the end, it was found that there was significant development to the students? average scores. The students? average score in pretest 56.4, the highest score was 83, and lowest score was 38. After the treatment, the average score was 64.6, the highest score was 95, and the lowest score was 50.   Keywords: Flashcards, Vocabulary, and Experimental.   Abstrak: Penelitian ini bertujuan untuk menemukan apakah flashcard dapat mengajarkan kosa kata mengenai objek kelas secara efektif kepada siswa. Populasi penelitian ini adalah seluruh siswa kelas tujuh di Sekolah Menengah Pertama No. 46 Palembang. Pengambilan sampel dilakukan dengan teknik convenient. Metode eksperimen dilaksanakan pada satu kelas sampel dengan prosedur pengajaran yang disusun. Siswa diberikan pembelajaran dengan menggunakan flashcard. Hasilnya menunjukkan bahwa adanya peningkatan pada nilai rata-rata siswa. Nilai rata-rata siswa pada saat pretes adalah 56.4, nilai tertinggi adalah 83, dan nilai terendah adalah 38. Setelah perlakuan menggunakan flashcard, peningkatan terlihat dari nilai rata-rata siswa 64.6, nilai tertinggi 95, dan nilai terendah 50.   Kata Kunci: Flashcards, Kosakata, dan Eksperimen.